Biogeographic Population Structure of Chimeric Blades of Porphyra in the Northeast Atlantic Reveals Southern Rich Gene Pools, Introgression and Cryptic Plasticity - Varela-Álvarez, Elena; Meirmans, Patrick G.; Guiry, Michael D.; Serrão, Ester A. (Frontiers in Plant Science, 2022)
The genus Porphyra sensu lato (Bangiaceae, Rhodophyta), an important seaweed grown in aquaculture, is the most genetically diverse group of the Class Bangiophyceae, but has poorly understood genetic variability linked to complex evolutionary processes. Genetic studies in the last decades have largely focused on resolving gene phylogenies; however, there is little information on historical population biogeography, structure and gene flow in the Bangiaceae, probably due to their cryptic nature, chimerism and polyploidy, which render analyses challenging. This study aims to understand biogeographic population structure in the two abundant Porphyra species in the Northeast Atlantic: Porphyra dioica (a dioecious annual) and Porphyra linearis (protandrous hermaphroditic winter annual), occupying distinct niches (seasonality and position on the shore). Here, we present a large-scale biogeographic genetic analysis across their distribution in the Northeast Atlantic, using 10 microsatellites and cpDNA as genetic markers and integrating chimerism and polyploidy, including simulations considering alleles derived from different ploidy levels and/or from different genotypes within the chimeric blade. For P. linearis, both markers revealed strong genetic differentiation of north-central eastern Atlantic populations (from Iceland to the Basque region of Northeast Iberia) vs southern populations (Galicia in Northwest Iberia, and Portugal), with higher genetic diversity in the south versus a northern homogenous low diversity. For. P. dioica, microsatellite analyses also revealed two genetic regions, but with weaker differentiation, and cpDNA revealed little structure with all the haplotypes mixed across its distribution. The southern cluster in P. linearis also included introgressed individuals with cpDNA from P. dioica and a winter form of P. dioica occurred spatially intermixed with P. linearis. This third entity had a similar morphology and seasonality as P. linearis but genomes (either nuclear or chloroplast) from P. dioica. We hypothesize a northward colonization from southern Europe (where the ancestral populations reside and host most of the gene pool of these species). In P. linearis recently established populations colonized the north resulting in homogeneous low diversity, whereas for P. dioica the signature of this colonization is not as obvious due to hypothetical higher gene flow among populations, possibly linked to its reproductive biology and annual life history.